2015
DOI: 10.1111/ctr.12520
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and events after liver transplantation. Experiences from 313 consecutive transplants with a follow‐up of 20 years

Abstract: Cardiovascular diseases (CVD) are the third leading cause of late death after liver transplantation (LT). The old PROCAM score was described in males (aged 35-65 yr) to estimate cardiovascular events after LT. New PROCAM is now available to estimate risks for cardiovascular events in both genders and for a wider age range (25-75 yr). We tested old and new PROCAM in long-term follow-up (10 and 20 yr) and described CVD risk factors, kidney function, and immunosuppression over two decades. A retrospective study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Numerous studies have demonstrated significant CV morbidity and mortality after liver transplantation . However, these outcomes vary across reports.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated significant CV morbidity and mortality after liver transplantation . However, these outcomes vary across reports.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal single‐institution study was performed to evaluate the risk and the incidence of CBVE over 20 years of follow‐up after LT. The cohort has already been described in detail in two other publications of our group …”
Section: Methodsmentioning
confidence: 99%
“…At primary LT, mean patient age was 45±11 years. Indications for primary transplants are presented in Table , but may also be reviewed in the abovementioned papers . Virus‐related cirrhosis (29.4%), alcoholic cirrhosis (16.0%), and cholestatic diseases (16.7%) were the most common indications for primary LT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(See Table 3, Ref. [1,55,78]) for comparison of CAR-OLT and PROCAM). They included 8 variables: smoking, LDL cholesterol, age, HDL cholesterol, family history of premature myocardial infarction, systolic blood pressure, triglycerides, and diabetes mellitus.…”
Section: Prediction Of Cardiovascular Events After Liver Transplantationmentioning
confidence: 99%